2014
DOI: 10.5455/njppp.2014.4.041220131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for eating disorders in Indian adolescent females

Abstract: Background: Eating disorders (ED) are one of the most common psychiatric problems faced by adolescents, and are characterized by a persistent course, comorbid psychopathology, medical complications, and elevated mortality. Aims & Objective: To assess the prevalence and correlates of eating disorders in a sample of adolescent Indian females. Materials and Methods: In a cross-sectional survey, 120 adolescents females (age: 13-17 years) filled out questionnaires on eating attitudes and behaviors at one independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
(13 reference statements)
1
24
0
1
Order By: Relevance
“…This finding was harmonious with a study conducted in Singapore 10.5% [11]. However, the finding was lower than the results of previous studies; in Northern Israel 5% of boys and 20.8% of girls [8], Northwest Iran 24.2% [9], Tabriz City 16.7% [10], Brazil 15.76% [12], Indian 26.67% [13] and South Africa 21.2% [15]. This observed discrepancy could be due to socio-demographic and cultural variations in the study areas.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…This finding was harmonious with a study conducted in Singapore 10.5% [11]. However, the finding was lower than the results of previous studies; in Northern Israel 5% of boys and 20.8% of girls [8], Northwest Iran 24.2% [9], Tabriz City 16.7% [10], Brazil 15.76% [12], Indian 26.67% [13] and South Africa 21.2% [15]. This observed discrepancy could be due to socio-demographic and cultural variations in the study areas.…”
Section: Discussionsupporting
confidence: 70%
“…Nonetheless, according to different studies the prevalence of disordered eating attitude has been widely documented: in Northern Israel 5% of boys and 20.8% of girls [8], Northwest Iran 24.2% [9], Tabriz City 16.7% [10], Singapore 10.5% [11], Brazil 15.76% [12], Indian 26.67% [13], Jeddah 32.9% [14] and South Africa 21.2% [15] of studied adolescents had disordered eating attitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of 120 schoolgirls aged 13–17 years in India found that 27% reported disordered eating behaviour, with higher EAT ‐ 26 scores significantly associated with dieting behaviours, drive for thinness and body dissatisfaction (Upadhyah et al . ). A survey of 66 psychiatrists practicing in an urban Indian town reported that two‐thirds of them had seen an ED case over the past year (Chandra et al .…”
mentioning
confidence: 97%
“…It was also observed that a higher proportion of participants with a high SCOFF score were in the 16-18 years age group compared to the 19-20 year-olds (Shaikh & Kayani 2014). A recent study of 120 schoolgirls aged 13-17 years in India found that 27% reported disordered eating behaviour, with higher EAT-26 scores significantly associated with dieting behaviours, drive for thinness and body dissatisfaction (Upadhyah et al 2014). A survey of 66 psychiatrists practicing in an urban Indian town reported that two-thirds of them had seen an ED case over the past year (Chandra et al 2012).…”
mentioning
confidence: 99%